IMPLIKASI DUALISME NORMA FIQH DAN HUKUM PERKAWINAN NASIONAL DALAM PERCERAIAN MASYARAKAT MANDAILING NATAL - Asrul Hamid; Raja Ritonga; Ilham Ramadan Siregar; Andri Muda Nst; Zuhdi Hsb (IAIN BONE, 2026)
This study is motivated by the existence of normative dualism between fiqh and national marriage law in divorce practices within the Mandailing Natal community. Fiqh recognizes the validity of divorce (talak) pronounced outside the court as long as it fulfills the required pillars and conditions, whereas Indonesian marriage law requires that divorce be conducted through the Religious Court to obtain legal validity. This difference creates a normative tension between religious legitimacy and formal state legality, which affects social practices in society. This study aims to analyze the construction of divorce norms in fiqh and national marriage law, identify the forms of normative dualism in divorce practices in Mandailing Natal, and examine their implications for legal certainty and the protection of the parties’ rights. This research employs a socio-legal method with statutory and empirical approaches through interviews and observation. The findings reveal that normative dualism is manifested in the practice of divorce outside the court, settlement of divorce through family and customary mechanisms, and remarriage without an official divorce certificate. These conditions lead to legal uncertainty, weak protection of women’s and children’s rights, and administrative obstacles in social life. Therefore, harmonization efforts between fiqh and national law are necessary through educational, cultural, and institutional approaches to achieve legal certainty and justice.